Transfusion‐transmitted hepatitis B virus (HBV) infection from an individual‐donation nucleic acid (ID‐NAT) non‐reactive donor. Issue 3 (14th February 2018) - O'Flaherty, N.; Ushiro‐Lumb, I.; Pomeroy, L.; Ijaz, S.; Boland, F.; De Gascun, C.; Fitzgerald, J.; O'Riordan, J.
Abstract : Lookback was initiated upon notification of an acute HBV infection in a repeat Irish donor, 108 days post‐donation. The donation screened non‐reactive by individual‐donation nucleic acid testing (ID‐NAT) using the Procleix Ultrio Elite multiplex assay and again when the archived sample was retested, but the discriminatory assay for HBV was reactive. The immunocompromised recipient of the implicated red cell component was tested 110 days post‐transfusion, revealing a HBV DNA viral load of 470 IU/ml. Genotype C2 sequences identical across two regions of the HBV genome were found in samples from the donor and recipient.